Revealing the geoheritage of Eastern Crete, through the development of Sitia Geopark, Crete, Greece - Fassoulas, C.; Staridas, S.; Perakis, V.; Mavrokosta, C. (Bulletin of the Geological Society of Greece, 2013)
In the present document we present the main studies, actions, initiatives and infrastructure developed under the project GEOTOPIA aiming to develop a geopark at the easternmost part of Crete, in Sitia area. The developed activities may be considered as model to establish a geopark in a rural area under the provisions of European and Global Geoparks Networks, aiming intimately to a responsible tourist development. Study area includes the eastern coastal zone of Sitia municipality extended westwards to the Sitia mountains. It presents an impressive geological heritage constituted mainly by the landscape variations (including gorges, plateaus and long cave systems), hydrological resources, rock types and abundant mammal fossils. The project resulted in an inventory, mapping and evaluation of geotopes using existing methodologies, in undertaking conservation, educational and geotourisitc activities, among them the development of two educational projects, two local museums, 15 geotrails, outdoor panels and signposts, as well as printed, visual and web material. A management and action plan has been also conducted presenting the goals, the methodologies, the resources and the timetable to manage the area as a real geopark. Furthermore, the plan foresaw the interaction of geopark initiative in respect to other planned investments and activities in the area.